The Avengers. Vol. 1, The Impossible City - MacKay, Jed; MacKay, Jed, 1983- (Marvel Worldwide, Inc., a subsidiary of Marvel Entertainment, LLC, 2023)
A brand-new era for Earth's Mightiest Heroes begins here! Jed MacKay and Stormbreaker C.F. Villa take the reins of Earth's Mightiest Heroes! The Star. The Icon. The Witch. The Construct. The God. The Engineer. The King. The world is ever in peril, and a new team of Avengers mobilizes to meet any dangers that dare threaten the planet. But when Terminus attacks, a new and insidious danger rears its head: one that the Avengers know all too well, and one that comes to them in the most dangerous of guises - that of a friend. Collecting: Avengers (2023) 1-6.